Pretomanid Pharmacokinetics in the Presence of Rifamycins: Interim Results from a Randomized Trial among Patients with Tuberculosis - Ignatius, Elisa H. (Antimicrob Agents Chemother, 2021)
Shorter, more potent regimens are needed for tuberculosis. The nitroimidazole pretomanid was recently approved for extensively drug-resistant tuberculosis in combination with bedaquiline and linezolid. Pretomanid may also have benefit as a treatment-shortening agent for drug-sensitive tuberculosis. It is unclear how and whether it can be used together with rifamycins, which are key sterilizing first-line drugs. In this analysis, data were pooled from two studies: the Assessing Pretomanid for Tuberculosis (APT) trial, in which patients with drug-sensitive pulmonary TB received pretomanid, isoniazid, and pyrazinamide plus either rifampin or rifabutin versus standard of care under fed conditions, and the AIDS Clinical Trials Group 5306 (A5306) trial, a phase I study in healthy volunteers receiving pretomanid alone or in combination with rifampin under fasting conditions. In our population pharmacokinetic (PK) model, participants taking rifampin had 44.4 and 59.3% reductions in pretomanid AUC (area under the concentration-time curve) compared to those taking rifabutin or pretomanid alone (due to 80 or 146% faster clearance) in the APT and A5306 trials, respectively. Median maximum concentrations (C(max)) in the rifampin and rifabutin arms were 2.14 and 3.35 mg/liter, while median AUC(0–24) values were 30.1 and 59.5 mg·h/liter, respectively. Though pretomanid exposure in APT was significantly reduced with rifampin, AUC(0–24) values were similar to those associated with effective treatment in registrational trials, likely because APT participants were fed with dosing, enhancing pretomanid relative bioavailability and exposures. Pretomanid concentrations with rifabutin were high but in range with prior observations. While pretomanid exposures with rifampin are unlikely to impair efficacy, our data suggest that pretomanid should be taken with food if prescribed with rifampin. (This study has been registered at ClinicalTrials.gov under identifier NCT02256696.)